Zinc-finger antiviral protein-mediated inhibition of porcine epidemic diarrhea virus growth is antagonized by the coronaviral nucleocapsid protein - Sungsuwan, Suttipun; Kadkanklai, Supasek; Mhuantong, Wuttichai; Jongkaewwattana, Anan; Jaru-Ampornpan, Peera (Frontiers in Microbiology, 2022)
Coronaviruses have long posed a major threat not only to human health but also to agriculture. Outbreaks of an animal coronavirus such as porcine epidemic diarrhea virus (PEDV) can cause up-to-100% mortality in suckling piglets, resulting in devastating effects on the livestock industry. Understanding how the virus evades its host’s defense can help us better manage the infection. Zinc-finger antiviral protein (ZAP) is an important class of host antiviral factors against a variety of viruses, including the human coronavirus. In this study, we have shown that a representative porcine coronavirus, PEDV, can be suppressed by endogenous or porcine-cell-derived ZAP in VeroE6 cells. An uneven distribution pattern of CpG dinucleotides in the viral genome is one of the factors contributing to suppression, as an increase in CpG content in the nucleocapsid (N) gene renders the virus more susceptible to ZAP. Our study revealed that the virus uses its own nucleocapsid protein (pCoV-N) to interact with ZAP and counteract the activity of ZAP. The insights into coronavirus-host interactions shown in this work could be used in the design and development of modern vaccines and antiviral agents for the next pandemic.